Sexual Ethics, Medical Risks, and Marital Harmony: An Analysis of Oral Sex from the Perspectives of Bioethics and Islamic Family Law - Abdulraheem Abdulwahid Yusuph; Isa Olawale Solahudeen (Legitima : Jurnal Hukum Keluarga Islam, 2025)
Purpose – This article discusses the practice of oral sex in marriage as a contemporary issue that reveals normative tensions between medical bioethics and Islamic family law. This study aims to analyze the practice of oral sex not only from the perspective of Islamic law but also by considering the medical risks, sexual ethical dimensions, and its impact on husband-wife relations within the framework of contemporary Islamic family law. Methods – This qualitative study with a normative legal research type uses an interdisciplinary approach, including fiqh and Islamic family law approaches, Islamic bioethics, and medical bioethics studies based on international scientific literature. Data were obtained through a literature study of classical and contemporary Islamic legal sources, as well as national and international journal articles in the fields of bioethics and sexual health, which were analyzed normatively, analytically, and comparatively using the maqāṣid al-sharī‘ah framework. Findings – This study confirms that the practice of oral sex in marriage must be analyzed multidimensionally, considering medical risks, sexual ethics, and the quality of the husband-wife relationship. Medical bioethics findings indicate potential health risks that require caution, while Islamic bioethics and maqāṣid al-sharī‘ah provide a normative framework that emphasizes the protection of life, human dignity, and family welfare. Simultaneously, contemporary Islamic family law analysis reveals that the impact of oral sex on marital relations is highly dependent on the principles of equal consent, open communication, and balance of power in the relationship. Research implications – This finding implies the need for a reconstruction of sexual ethics in Islamic family law that is not permissive without limits but also does not reject medical science findings, instead integrating them critically for the benefit of the family. Originality/value – The originality of this research lies in its integrative approach to examining oral sex through a synthesis of medical bioethics, Islamic bioethics, and contemporary Islamic family law, thereby offering a more comprehensive and relevant normative-ethical perspective on Islamic law in the modern era.